2015
DOI: 10.1002/elps.201500195
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic manipulation of particle mixtures employing asymmetric insulating posts

Abstract: A novel scheme for particle separation with insulator-based dielectrophoresis (iDEP) was developed. This technique offers the capability for an inverted order in particle elution, where larger particles leave the system before smaller particles. Asymmetrically shaped insulating posts, coupled with direct current (DC) biased low-frequency alternating current (AC) electric potentials, were used to successfully separate a mixture of 500 nm and 1 μm polystyrene particles (size difference of 0.5 μm in diameter). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…(H) Enrichment of yeast cells in a microdevice with asymmetric posts, the two images illustrate the outlet of the post array where yeast cells (labelled green) accumulated for their subsequent release and elution. Reprinted from , copyright (2015) John Wiley and Sons. (I) Illustration of an EπDEP device depicting the embedded passivated electrodes (600 μm wide) and two columns of cylindrical insulating posts within.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 99%
See 1 more Smart Citation
“…(H) Enrichment of yeast cells in a microdevice with asymmetric posts, the two images illustrate the outlet of the post array where yeast cells (labelled green) accumulated for their subsequent release and elution. Reprinted from , copyright (2015) John Wiley and Sons. (I) Illustration of an EπDEP device depicting the embedded passivated electrodes (600 μm wide) and two columns of cylindrical insulating posts within.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 99%
“…A sinusoidal AC signal with a positive DC bias was utilized to separate a sample containing 1 and 2 μm polystyrene particles and yeast cells in 120 s. The particles were enriched and separated in “dielectropherogram” scheme. In a more recent contribution, this group reported the use of asymmetric posts to invert particle elution order when carrying out a particle separation process . By carefully designing a custom DC‐biased AC signal, this group was able to enrich and selectively elute first the larger particles present in a mixture.…”
Section: Advances On Devices For Trapping Idepmentioning
confidence: 99%
“…iDEP is a particle confining technique based on the movement of matter in inhomogeneous electric fields that employs insulating structures embedded in a microchannel to produce electric field gradients [36,37,38,39]. The inhomogeneous electric field required for iDEP platforms is induced when the cross-sectional area of the microchannel is “pinched” by the presence of electrically insulating structures between external electrodes [38].…”
Section: Dep Backgroundmentioning
confidence: 99%
“…While in [38], the iDEP showed that particles’ size and the shape of microelectrode have significant effects on the magnitude, location, and shape of the DEP trapping regions. On the other hand, in [39] the researchers were able to segregate certain bio-particles by using asymmetric shaped insulating posts coupled with low-frequency electric potentials. Moreover, the electrodes in [40] were fabricated onto quartz substrates using photolithography technique and were used for the direct mapping of the suspended particles’ spatial concentrations.…”
Section: Dep Backgroundmentioning
confidence: 99%
“…Unlike traditional DEP, cDEP does not require the electrodes to be in direct contact with the cell suspension, but rather uses fluidic electrodes containing an electrolyte solution separated from the main cell‐flow channel by a thin membrane. Separating the electrodes from the fluid in the device eliminates electrolysis and improves cell viability by preventing cell‐to‐electrode contact . Analogous to insulator‐based DEP (iDEP), insulating posts within the channel create gradients in the electric field that drive the DEP force .…”
Section: Introductionmentioning
confidence: 99%